2016
DOI: 10.1051/e3sconf/20160720011
|View full text |Cite
|
Sign up to set email alerts
|

Supporting decision-making for channel conveyance maintenance

Abstract: Abstract. Channel maintenance activities, understood as vegetation and sediment management, have a potential to change the conveyance capacity of a watercourse and thus, to provide a benefit from a flood risk perspective. Vegetation and its overgrowth is one of the main factors influencing flow capacity and hence river conveyance. Despite the undesirable consequences associated with flooding, it is rare that sufficient funds are available to undertake all necessary maintenance activities. In the face of limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These problems are complicated in Egypt by the division between the main irrigation system, outflow command, and drainage. Determining the farmers' participation, or alternatively, the extent of government engagement in funding as well as in duties for execution and control of maintenance at the outflow command level and in downstream drainage would be crucial subjects [55,56].…”
Section: Comparison Between the Literature And The Measured Dcr For E...mentioning
confidence: 99%
“…These problems are complicated in Egypt by the division between the main irrigation system, outflow command, and drainage. Determining the farmers' participation, or alternatively, the extent of government engagement in funding as well as in duties for execution and control of maintenance at the outflow command level and in downstream drainage would be crucial subjects [55,56].…”
Section: Comparison Between the Literature And The Measured Dcr For E...mentioning
confidence: 99%
“…This is because smoother surfaces have lower roughness coefficient and less retarding effect on the water flow, hence a higher rate is produced and it can be concluded that flow rate and roughness coefficient were influenced by bed roughness and slope. Also, an increase of flow resistance involves smaller flow velocities and greater water depths (Roca et al, 2016). The experiment was performed in a flume with a fixed boundary where the area is constant.…”
Section: Effects Of the Soil Boundary Influence On The Velocity Of Flow For Both Riversmentioning
confidence: 99%
“…The study reveals that soil gradation has a major effect on the efficiency of removing deposits by the jet pump. Roca, Rushworth, and Dennes (2016) studied the potential of vegetation and sediment management on the conveyance capacity of a watercourse. The study presents a national-scale approach (United Kingdome) to identify the strategically important watercourses where conveyance related works produce the greatest benefit.…”
Section: Introductionmentioning
confidence: 99%